Numerical investigation of the impact of warming blankets on the performance of ventilation systems in the operating room. Issue 5 (3rd September 2022) - Sadeghian, Parastoo; Duwig, Christophe; Sköldenberg, Olof; Tammelin, Ann; Hosseini, Ardalan Rahimi; Sadrizadeh, Sasan
ABSTRACT: Patient warming is an efficient approach to preventing hypothermia during surgeries. Hypothermia increases the risk of postoperative infections, bleeding, transfusion demand, prolonging postoperative recovery, drug metabolism duration and vasoconstriction. Although the use of warming blankets addresses the problem of a decrease in a patient's core body temperature, concern remains that the heat emitted by these warming blankets can disturb the supplied clean air by the ventilation system and thus increase the contamination level of airborne particles. The main purpose of this study is to numerically investigate the impact of using warming blankets on the performance of two common ventilation systems – unidirectional flow and mixing ventilation – in an operating room. The effect of using forced-air and conductive warming blankets on the distribution of bacteria-carrying particles and airflow behaviour were simulated in the operating room. The results showed that applying the forced-air warming blanket considerably increased the average air temperature at the wound area and under the surgical drape. Thus, the forced-air warming blanket can be more effective than the conductive blankets in warming the patient during the surgery. However, using the contaminated forced-air warming blanket resulted in a considerable increase in the contamination concentration at the wound surface.